Pertanggungjawaban Hakim atas Pelanggaran Kode Etik dan Tindak Pidana dalam Kasus Rechterlijke Dwaling di Indonesia (Studi Kasus Putusan Pengadilan Negeri Surabaya Nomor 454/Pid.B/2024/PN.Sby) - Susanto, Heri; Kemala, Ratih (HUMANIORUM, 2025)
Rechterlijke dwaling is a failure of the law enforcement process that injures the sense of justice and diminishes public trust in the judicial system. The role of the judge, as the person fully responsible for the course of the trial, in upholding the law and justice is very crucial. However, it is not uncommon for cases where judges violate the code of ethics or even commit crimes causing rechterlijke dwaling. This journal discusses how judges are accountable both in the ethical and criminal realms in cases of rechterlijke dwaling, as well as the relevance of decision number 454 / Pid.B / 2024 / PN.Sby to this. This study found two things, namely; 1). the existence of a conflict of norms related to the criminal responsibility of judges, which shows the need to strengthen regulations as an effort to prevent the occurrence of rechterlijke dwaling, 2). decision number 454 / Pid.B / 2024 / PN.Sby is a miscarriage of decision which is caused by rechterlijke dwaling in its legal considerations.